Coma associated with microscopy-diagnosed Plasmodium vivax: a prospective study in Papua, Indonesia. - Daniel A Lampah; Tsin W Yeo; Setiawan O Hardianto; Emiliana Tjitra; Enny Kenangalem; Paulus Sugiarto; Ric N Price; Nicholas M Anstey (PLoS Neglected Tropical Diseases)
Background Coma complicates Plasmodium falciparum infection but is uncommonly associated with P. vivax. Most series of vivax coma have been retrospective and have not utilized molecular methods to exclude mixed infections with P. falciparum. Methods We prospectively enrolled patients hospitalized in Timika, Indonesia, with a Glasgow Coma Score (GCS) ≤10 and P. vivax monoinfection on initial microscopy over a four year period. Hematological, biochemical, serological, radiological and cerebrospinal fluid (CSF) examinations were performed to identify other causes of coma. Repeat microscopy, antigen detection and polymerase chain reaction (PCR) were performed to exclude infections with other Plasmodium species. Results Of 24 patients fulfilling enrolment criteria, 5 had clear evidence for other non-malarial etiologies. PCR demonstrated 10 mixed infections and 3 P. falciparum monoinfections. 6 (25%) patients had vivax monoinfection and no apparent alternative cause, with a median GCS of 9 (range 8-10) and a median coma duration of 42 (range 36-48) hours. CSF leukocyte counts were <10/ul (n=3); 2 of the 3 patients without CSF examination recovered with antimalarial therapy alone. One patient had a tremor on discharge consistent with a post-malarial neurological syndrome. No patient had other organ dysfunction. The only death was associated with pure P. falciparum infection by PCR. Vivax monoinfection-associated risk of coma was estimated at 1 in 29,486 clinical vivax infections with no deaths. In comparison, the risk of falciparum-associated coma was estimated at 1 in 1,276 clinical infections with an 18.5% mortality rate. Conclusions P. vivax-associated coma is rare, occurring 23 times less frequently than that seen with falciparum malaria, and is associated with a high proportion of non-malarial causes and mixed infections using PCR. The pathogenesis of coma associated with vivax malaria, particularly the role of comorbidities, is uncertain and requires further investigation.